Pengaruh Alat Peraga Kampanye dan Media Sosial Terhadap Preferensi Masyarakat di Kabupaten Wonosobo tahun 2024 - latif abdurochman; Irwan Abdu Nugroho (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The use of conventional campaign props and social media in the 2024 General Election reflects a new dynamic in the practice of Indonesian democracy, where both mediums play a significant role in shaping public opinion and voter preferences. Amidst the rise of digitalization, the effectiveness of social media as a campaign channel has contributed to a shift in political communication patterns compared to conventional methods, which continue to spark controversy.This study aims to analyze the influence of conventional campaign props and social media on the formation of voter preferences in Wonosobo Regency during the 2024 General Election. The research employed a quantitative method. The results revealed that both factors significantly influenced public preferences in Wonosobo Regency. There is a correlation between campaign props and social media with public preferences, as indicated by the multiple regression coefficients of 0.631 for campaign props and 0.057 for social media. Furthermore, the combined contribution of both factors to public preferences reached 53%, based on the determination value. Based on the t-test results, campaign props had a significant influence with a significance value of 0.046, while social media also showed a significant impact with a significance value of 0.042. Additionally, the F-test indicated that campaign props and social media simultaneously affected voter preferences, with a significance value of 0.043